Bio-efficacy of DuraNet® long-lasting insecticidal nets against wild populations of Anopheles arabiensis in experimental huts - Aneth M. Mahande; Shandala Msangi; Lucile J. Lyaruu; Eliningaya J. Kweka (Tropical Medicine and Health, 2018)
Abstract Background Mosquitoes have developed resistance to multiple classes of insecticides for malaria vector control. A new generation of long-lasting insecticidal bed nets (LLINs) has been developed with increased efficacy against these resistant mosquitoes. The present study therefore evaluated the efficacy of the pyrethroid-based LLINs, DuraNet versus PermaNet 3.0, in an Eastern Africa hut design in Magugu in northern Tanzania where mosquitoes’ population higher proportion (69.3%) has been identified as Anopheles gambiae s.l. Methods Standard World Health Organization bioefficacy evaluations were conducted in both laboratory and experimental huts. Experimental hut evaluations were conducted in an area with high populations of Anopheles arabiensis. All nets used were subjected to laboratory cone bioassays and then to experimental hut trials. Mosquito mortality, blood-feeding inhibition, and personal protection rate were compared between untreated nets, unwashed LN, and LN that were washed 20 times. Results Standard WHO laboratory bioefficacy evaluations of DuraNet and PermaNet® 3.0 which were untreated, washed, or 20 times washed showed optimal knockdown and mortality for both net types against a susceptible strain of An. arabiensis. In standard experimental hut evaluations, the blood feeding inhibition for PermaNet® 3.0 unwashed and washed was 82.4% (76.3–88.6%) to 91.5% (84.1–98.8%) while for DuraNet was 98.3% (97.0–99.5%) to 96.0% (94.1–88.2%) respectively. The DuraNet LLINs showed a significantly higher killing effect than the other treatment of 90.0% (86.1–94.2%) and 94.0% (90.2–97.9%) for unwashed and washed nets respectively. No significant difference in deterrence or induced exophily was detected between the treatment arms. There were no adverse effects reported among sleepers in the experimental huts. Conclusion The findings of this study indicate that the pyrethroid-based net DuraNet LLINs attained required efficacy when evaluated against wild population of An. arabiensis from Northern Tanzania. ...